PENGARUH LITERASI MEMBACA TERHADAP PRESTASI BELAJAR SISWA KELAS VIII MATA PELAJARAN ILMU PENGETAHUAN SOSIAL DI SMP NEGERI 34 KOTA BEKASI - FATHMA HAMIDAH; EKA PUTRI; UZA SUKMANA (GANEC SWARA, 2024)
This research aims to determine the effect of reading literacy on the learning achievement of eighth-grade students in the subject of Social Sciences (IPS) at SMP Negeri 34 in Bekasi City. In this study, the method used is a quantitative method with a descriptive approach. The sampling technique used is random sampling taken from the total population of class VIII A-I randomly, with a total sample of 79 students. The analysis technique used is simple linear regression. The results of the analysis of the coefficient of determination test in the model summary show an R square value of 0.135, which means that the influence of reading literacy on student learning achievement is 13.5%. The theoretical and practical implications suggest that by developing reading materials, schools should ensure the availability of relevant and engaging reading sources to enhance reading literacy activities at SMP Negeri 34 in Bekasi City. This research makes a significant contribution to the understanding of the critical role of reading skills in improving the academic performance of eighth-grade students in Social Studies